2017
DOI: 10.2981/wlb.00238
|View full text |Cite
|
Sign up to set email alerts
|

Emerging technology to measure habitat quality and behavior of grouse: examples from studies of greater sage-grouse

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…As Patricelli and Krakauer (2010) found with the first-generation robot, we found that males responded to our second-generation robot in a similar way as they would to a typical real female. Specifically, individual males' estimated tendencies to continue a display bout (i.e., their display effort) with the robot and with real females are strongly related (R 2 p 0:72; N p 96 males; Forbey et al 2017).…”
Section: Robotic Female and Experimental Protocolmentioning
confidence: 99%
See 2 more Smart Citations
“…As Patricelli and Krakauer (2010) found with the first-generation robot, we found that males responded to our second-generation robot in a similar way as they would to a typical real female. Specifically, individual males' estimated tendencies to continue a display bout (i.e., their display effort) with the robot and with real females are strongly related (R 2 p 0:72; N p 96 males; Forbey et al 2017).…”
Section: Robotic Female and Experimental Protocolmentioning
confidence: 99%
“…These observations overlapped temporally with our experiments (10 nonconsecutive days between April 5 and May 3, between 0539 and 0718 hours). We used these data to compare males' display effort during interactions with robotic versus real females (Forbey et al 2017) and to characterize how males' display effort changed as the breeding season progressed.…”
Section: Natural Courtship Datamentioning
confidence: 99%
See 1 more Smart Citation
“…However, for sUAS to be effective, they need to collect accurate counts of individual grouse through imagery. Research using sUAS on greater sage-grouse Centrocercus urophasianus suggests still imagery are of sufficiently high resolution to detect individual males on leks (Hanson et al 2014, Forbey et al 2017. Prairie grouse Tympanuchus spp.…”
mentioning
confidence: 99%
“…( Mulero-Pázmány et al, 2014;Chrétien et al, 2016;Hodgson et al, 2016;Weissensteiner et al, 2015;Goebel et al, 2015Habel et al, 2016Forbey et al, 2017)…”
Section: Uav Applicationmentioning
confidence: 99%